Prevalence of iron depletion and anemia in Hong Kong female athletes - Siu, P.-I. F.; Chung, S. (Research Highlights, 2021)
The purpose of this study is to investigate the prevalence of iron depletion and anemia in Hong Kong female athletes. Iron plays an important role in exercise performance. Iron depletion or iron deficiency is one of the most prevalent nutrient deficiencies in athletes [1,2] . The prevalence of iron depletion in Hong Kong female athletes was similar to other studies [1,2] . No significant difference was found among different sports groups suggesting that different forms of training may not affect iron status of female athletes in Hong Kong. Iron depletion or iron deficiency is preventable. It is recommended that athletes, particularly with past medical history of low iron stores, should regularly monitor their iron status.